MiRNAs roles in the diagnosis, prognosis and treatment of colorectal cancer. (3rd October 2019) - Sur, Daniel G.; Colceriu, Marius; Sur, Genel; Aldea, Cornel; Silaghi, Ciprian; Samasca, Gabriel; Lupan, Iulia; Căinap, Călin; Burz, Claudia; Irimie, Alexandru
ABSTRACT: Introduction : The liver is the main location for metastasization in stage IV colorectal cancers. Areas covered : This review intends to comprehensively present the most important studies conducted in the past few years concerning the role of miRNAs in colorectal cancer liver metastases, trying to clarify some aspects regarding tumor biology and favorite liver metastasization site. Expert commentary : Recent advances in tissue and serum RNA extraction has considerably improved the field of microRNAs studies. These molecules known to play a crucial role in the metastatic stage indicate a starting point in the development of clinical biomarkers with a possible role in the stratification of high-risk patients for adequate treatment.